Solitary neurofibroma of the hard palate - Orsola Brucoli; Eleonora Rivetti; Paolo Boffano (Journal of Dentomaxillofacial Science, 2022)
Neurofibromas are benign tumors of the peripheral nerve sheath that unfrequently affect head and neck.  They can be solitary when not associated with any syndrome or multiple if they are associated with autosomal dominant neurofibromatosis syndrome. They can also be classified as myxomatous (solid, central, diffuse) or plexiform (peripheral). Neurofibromas may be intra or extra-osseous. Most common extra-osseous oral sites are tongue, oral mucosa and lips. In the literature, few cases of solitary extra-osseous neurofibromas of the palate have been documented. In this article, we present the diagnosis and management of a neurofibroma of the palate.